2008
DOI: 10.1002/pd.2064
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of MCP‐1 are increased in women with gestational diabetes

Abstract: The elevation of MCP-1 in the third trimester in gestational diabetes mellitus suggests an association between inflammation and GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
5
26
0
Order By: Relevance
“…Clinically, results from previous studies have also indicated that MCP1 is elevated during pregnancy and further augmented in GDM compared with NTG. Consistent with the results reported by Klein et al (2008), our clinical detection of MCP1 also found elevated MCP1 concentration in GDM women; moreover, elevated MCP1 is associated with abnormal glucose tolerance. Although it has been proposed that this inflammation is mediated by the placenta (Klein et al 2008), our results confirmed that elevated MCP1 levels in pregnancy were produced by increased fat mass under surged CG stimulation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Clinically, results from previous studies have also indicated that MCP1 is elevated during pregnancy and further augmented in GDM compared with NTG. Consistent with the results reported by Klein et al (2008), our clinical detection of MCP1 also found elevated MCP1 concentration in GDM women; moreover, elevated MCP1 is associated with abnormal glucose tolerance. Although it has been proposed that this inflammation is mediated by the placenta (Klein et al 2008), our results confirmed that elevated MCP1 levels in pregnancy were produced by increased fat mass under surged CG stimulation.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, prepregnancy BMI in GDM subjects was higher than that of NGT subjects (25.83G2.7 versus 23.85G2.62), and prepregnancy BMI was associated with fasting (P!0.0001) and 1-h (PZ0.002) glucose levels ( Table 3). Results of ELISA assays also indicated that MCP1, a key factor in the recruitment and activation of peripheral blood leukocytes, was elevated in GDM woman compared with healthy pregnant women (83.71G21.1 versus 100.72G32.82 pg/ml), which was consistent with previous report (Klein et al 2008). Furthermore, MCP1 levels were associated with abnormal 1-(PZ0.025) and 2-h (PZ0.008) post glucose load (Table 3).…”
Section: Cg Modulates Proinflammatory Cytokines In 3t3-l1 Adipocytessupporting
confidence: 80%
“…TNFa, which is a significant predictor of insulin resistance during pregnancy [38], is higher in pregnant women with GDM when compared to NGT women [36,37]. Similarly, other circulating proinflammatory cytokines like MCP-1 [35], IL-1b [40] and IL-6 [31,41,59] are also positively correlated with GDM. Therefore, it is possible, that maternal systemic inflammation associated with GDM may induce the expression of placental Nurr1 and Nur77.…”
Section: Discussionmentioning
confidence: 85%
“…An overproduction of placental TNF-a have been demonstrated in patients with GDM [39] and is associated with increased fetal adiposity [29]. Other circulating pro-inflammatory cytokines like monocyte chemoattractant protein-1 (MCP-1) [35], IL-1b [40] and IL-6 [41] are also positively correlated with GDM. Notably, the upstream factors involved in the regulation of these pro-inflammatory cytokines in human placenta are not known.…”
Section: Introductionmentioning
confidence: 97%
“…Low-grade maternal inflammation is a key feature of pregnancies complicated by GDM [3339]. There is extensive evidence that show human placenta and adipose tissue are important sites involved in the propagation of this maternal inflammation [15, 21, 22, 30, 32, 4048].…”
Section: Discussionmentioning
confidence: 99%